Los intelectuales colombianos y el dilema de la construcción de la identidad nacional (1850-1930) - Charry Joya, Carlos Andrés (European Review of Latin American and Caribbean Studies, 2011)
Colombia’s intellectuals and the dilemma of constructing a national identity (1850-1930)The article explores and analyses the different discursive approaches produced by the main representatives of the Colombian intellectuals in relation to the theme of people and nation, from the mid-nineteenth century to the first decades of the twentieth. To do so, a broad analysis is made which includes the expressions of well-known personalities such as Miguel María Samper and Miguel Antonio Caro up to a very detailed evaluation of the origins and repercussions of eugenic discourse represented by intellectuals such as Miguel Jiménez López and Luis López de Mesa in the 1920s.Resumen:El artículo explora y analiza los diferentes modos de aproximación discursiva producidos por los principales representantes de la intelectualidad colombiana en relación al tema del pueblo y la nación, entre mediados del siglo XIX y las primeras décadas del siglo XX. Para tal fin se hace un recorrido analítico desde las expresiones de personajes como Miguel María Samper y Miguel Antonio Caro, hasta llegar a evaluar con mayor detenimiento los orígenes y repercusiones del discurso eugenésico, representado por intelectuales tales como Miguel Jiménez López y Luis López de Mesa en la década de 1920.